Advances in capillary electrophoresis-mass spectrometry for pharmaceutical analysis (Asian Journal of Pharmaceutics (AJP), 2025)
Capillary electrophoresis-mass spectrometry (CE-MS) combines the high separation efficiency of capillaryelectrophoresis with the exceptional sensitivity and specificity of mass spectrometry. CE-MS has gained significanttraction in pharmaceutical analysis, offering unique advantages in the analysis of pharmaceuticals, biologics, andtheir metabolites. Recent technological advancements have enhanced CE-MS applicability, addressing historicalchallenges in interface design and improving system robustness and sensitivity. Novel capillary coatings andbackground electrolytes have expanded the range of analyzable compounds. CE-MS is utilized across various stagesof drug development and quality control, proving valuable in small-molecule drug analysis, and offering highresolutionseparations of structural isomers and chiral compounds. In biopharmaceuticals, CE-MS has emerged as apowerful tool for characterizing complex protein therapeutics, including monoclonal antibodies and biosimilars. Thetechnique provides detailed information on post-translational modifications and higher-order structures, ensuringbiologic drug quality and safety. CE-MS has shown potential in metabolomics, contributing to drug metabolismunderstanding and biomarker discovery. The technique’s minimal sample and solvent requirements align with greenanalytical chemistry principles. Ongoing research focuses on improving sensitivity, throughput, and data analysiscapabilities. Integration with other analytical techniques and advancements in bioinformatics tools are enhancingCE-MS applications in pharmaceutical analysis, particularly in the era of personalized medicine and biologics.